Effects of overweight on serum 25-hydroxyvitamin D macro and microelements and hematological parameters in healthy adult client-owned cats - Elham Valavi; Mehrdad Mohri (Scientific Reports)
Abstract Minerals and trace elements are crucial for maintaining normal body metabolism, but limited knowledge exists about their connection to being overweight in cats. This study was conducted to evaluate potential changes in hematological factors and the levels of minerals or trace elements in the serum of overweight cats. A cross-sectional study was carried out, and seventy-two client-owned, healthy adult cats were randomly selected from those visiting veterinary clinics in Mashhad. The cats were divided into two groups on the basis of their Body Condition Score (BCS): the ideal weight group (BCS = 5) and the overweight group (BCS ≥ 6). Serum concentrations of calcium, phosphorus, iron, magnesium, zinc, copper, and 25(OH) vitamin D and hematological parameters, including red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin, mean corpuscular hemoglobin (MCH), corpuscular hemoglobin concentration (MCHC), hematocrit, mean corpuscular volume (MCV), and red cell distribution width (RDW), were measured. Correlations between the variables were also determined. Overweight cats had significantly higher levels of iron, hematocrit, hemoglobin, RBC, and MCHC. Conversely, the levels of phosphorus, RDW, WBC, neutrophils, and monocytes were significantly lower in overweight cats than in those with ideal body weights. There were no significant differences in the other parameters measured between overweight and ideal-weight cats. Additionally, in the entire population and the normal-weight group, 25(OH) vitamin D showed a positive correlation with calcium and a negative correlation with magnesium. In conclusion, being overweight in cats causes changes in their hematological parameters and the concentrations of certain elements in blood serum, specifically iron and phosphorus. These changes were in reference interval thus, the clinical significance of these alterations requires further investigation especially in obese cats.